Efficacy of prednisone for the treatment of ocular myasthenia (EPITOME): A randomized, controlled trial. Issue 3 (27th January 2016) - Benatar, Michael; Mcdermott, Michael P.; Sanders, Donald B.; Wolfe, Gil I.; Barohn, Richard J.; Nowak, Richard J.; Hehir, Michael; Juel, Vern; Katzberg, Hans; Tawil, Rabi; ,
ABSTRACT: Introduction : In this study we evaluated the safety, tolerability, and efficacy of prednisone in patients with ocular myasthenia gravis (OMG) concurrently treated with pyridostigmine. Methods : This investigation was a randomized, double‐blind, placebo‐controlled trial. Participants whose symptoms failed to remit on pyridostigmine were randomized to receive placebo or prednisone, initiated at 10 mg every other day, and titrated to a maximum of 40 mg/day over 16 weeks. The primary outcome measure was treatment failure. Results : Fewer subjects were randomized than the 88 planned. Of the 11 randomized, 9 completed 16 weeks of double‐blind therapy. Treatment failure incidence was 100% (95% CI 48%–100%) in the placebo group ( n  = 5) vs. 17% (95% CI 0%–64%) in the prednisone group, P = 0.02 ( n  = 6). Median time to sustained minimal manifestation status (MMS) was 14 weeks, requiring an average prednisone dose of 15 mg/day. Adverse events were infrequent and generally mild in both groups. Conclusions : A strategy of low‐dose prednisone with gradual escalation appears to be safe, well‐tolerated, and effective in treating OMG. Muscle Nerve 53: 363–369, 2016